Ambon City Local Government Medium-Term Development (RPJMD): Culture Transmission Through Panas Pela of Education as A Peacebuilding - Asyrul Fikri; Anju Nofarof Hasudungan (Universitas Muhammadiyah Malang, 2021)
Pela Gandong local wisdom has played a significant role as a media for Ambon conflict resolution. The existence of dialogue and communication based on Pela Gandong culture can bring mutually battling parties to achieve peace. Therefore, the purpose of the study is to describe how SMPN 4 Salahutu Liang Central Maluku with 100% Muslim students also, SMPN 9 Ambon City with 99% of their Christian/Catholic students in implementing Panas Pela of Education as the transmission of Pela Gandong culture as an implementation of the Ambon City Regional Medium-term Development Plan (RPJMD). Panas Pela of education is an assemblage of students with different religions tore-warm the sibling relationship (Pela Gandong). This study uses descriptive qualitative research methods with a case study approach. Data collection is done by participatory observation, literature study, document analysis, and interviews. The results showed that the Panas Pela of Education activity on January 29, 2018, had succeeded in transmitting Pela Gandong culture to students to maintain peace. It can be seen by student’s ability from both schools to blend in with one another without segregation and together celebrate the Panas Pela of Education. It is expected that the field of education implementing Panas Pela of Education sustainably. It will surely be successful because the local wisdom of the Pela Gandong has been integrated into the Ambon City Local Government Medium-term Development Plan (RPJMD).